CATALASE ENZYME IN PLANT / A REVIEW ARTICLE (Web of Agriculture: Journal of Agriculture and Biological Sciences, 2024)
Enzymes work as a catalyst to speed up chemical reactions in plants and to ensure that the chemicals that are manufactured in the plant are the appropriate form, as molecules that have the same chemical formula can take two different forms that represent identical images of each other called isomers, as the catalase enzyme catalyzes the reaction that breaks hydrogen peroxide into water and oxygen. The level of constructive metabolism shows how much oxygen is produced over the time during which this reaction occurs with or without catalase. The reaction produces more oxygen in the presence of catalase use of enzymes an important role in stimulating chemical reactions, as they directly form gas bubbles, which is evidence that the test is positive (Catalase +ve), and if bubbles of oxygen gas do not rise, the result will be negative for this test (Catalase negative).